STUDY OF DRUGS FROM NATURAL ORIGIN USAGE IN THE ELDERLY AT GERIATRIC POLYCLINIC OF RSUP DR. SARDJITO YOGYAKARTA - Laksmi Maharani; Djoko Wahyono; I Dewa Putu Pramantara S (Faculty of Pharmacy, Universitas Gadjah Mada)
Complementary drugs usage has increased since the last 20 years. Complementary drugs are often used together with prescription drugs. Drugs from natural origin are not free from adverse effects. This study aimed to know drugs from natural origin usage in elderly at geriatric polyclinic of RSUP Dr. Sardjito Yogyakarta, the appropriateness of information received by patients, were potential interactions, adverse effects reaction.This study design was cross-sectional with purposive sampling technique. Data collected with questionnaire and medical record. Sample size which fulfilled inclusion criteria was 100 samples.The result showed that amount of drugs from natural origin usage in geriatric polyclinic of RSUP Dr. Sardjito Yogyakarta was 43%. The patient purposes in usage natural drugs were 63% as complement, 30% as supplement, and 7% as alternative. Patient characteristics which correlated with drugs from natural origin usage were gender (p<0.05) and occupation (p<0.05). Information received by patients, from friends or family 49%, advertisement 26%, health-care practitioners 16%, and their own knowledge 9%. Inappropriatness betwen patient purpose in using drugs with scientific evidence were 25% for supplement and 25% for complement and alternative. Potential interaction happened between bay leaves and lisinopril that caused hypertension. Adverse effect happened Holothuria sp. juice usage that caused allergic reaction and propolis usage that caused fever.Keywords : Drugs from natural origin, interactions, adverse effects